2023
DOI: 10.1055/s-0043-1761597
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Precontoured Titanium Mesh in the Reconstruction of Orbital Blowout Fractures

Abstract: Background Orbital blowout fractures are peculiar injuries causing disruption of both ocular function and symmetry. We present our experience with the use of a precontoured titanium mesh in orbital blowout fractures. Methods A retrospective study of patients undergoing correction of orbital blowout fractures with a precontoured titanium mesh was done at a tertiary care center in Mumbai. Data regarding demographics and pre- and postoperative clinical and radiological attributes were retrieved and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
0
0
Order By: Relevance
“…Despite the surgical intervention using titanium mesh, a notable proportion (11.6%) of patients continued to experience diplopia. This outcome aligns with existing literature suggesting that postsurgical diplopia remains a significant complication despite advances in surgical techniques (15). Titanium mesh's role in orbital floor reconstruction is critical, given its rigidity and compatibility with human tissue.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the surgical intervention using titanium mesh, a notable proportion (11.6%) of patients continued to experience diplopia. This outcome aligns with existing literature suggesting that postsurgical diplopia remains a significant complication despite advances in surgical techniques (15). Titanium mesh's role in orbital floor reconstruction is critical, given its rigidity and compatibility with human tissue.…”
Section: Discussionsupporting
confidence: 85%
“…In this investigation, titanium mesh was employed to stabilize orbital floor fractures. This follows a study published in 2023 (26), in which Munoli, Bhanushali and Jagannathan reported the precontoured titanium mesh that preserves the anatomy of the orbital wall and is quick, simple, repeatable, and has a low learning curve. Prefabricated titanium mesh can be a good reconstructive alternative for orbital fractures with careful patient selection and application (27).…”
Section: Discussionsupporting
confidence: 59%
“…Metallic materials, with titanium being the most widely used, remain the preferred gold standard for orbital floor reconstruction nowadays [27][28][29][30]. Titanium's exceptional biocompatibility, corrosion resistance, and mechanical properties closely resembling natural bone make it a preferred choice.…”
Section: Metalsmentioning
confidence: 99%